Critical analysis of the type section of the Balambo Formation (Valanganian-Turonian), Sirwan valley, Kurdistan Region, NE-Iraq - Karim, Kamal Haji; Al-Khafaf, Aras Omer; Sharbazheri, Khalid Mahmood Ismael (Sulaimani Journal for Pure and Applied Sciences)
The Balambo Formation (Garau Formation in Iran) and its equivalents such as Shuaiba, Qamchuqa and Mauddud are very significant formations since they occur nearly in all oil fields in Iraq and Iran. The first definition of its type section was carried out in 1947 in the Sirwan Valley on the southwestern limb of the Balambo Anticline, about 11 km to the southwest of Halabja town, 3 km to the east of Kawta village. In the present study, the first definition is critically analyzed in the field and laboratory by foraminifera and nannofossils aging. The analysis shows many problems in the thickness, stratigraphy, location and its relation to Kometan and Shiranish formations. Many structural and topographic characteristics (of the section) are shown to prove that the thickness of the type section is less than that indicated previously in the first definition. In the definition of the type locality, the Kometan Formation was not recorded, while the present study confirms its occurrence, with a thickness of about 80 m.. The lithological and Paleontological studies showed that the Kometan Formation has the age of Turonian – Late Campanian and has conformable contact with both Balambo and Shiranish formations. This does not coincide with the definition, which did not mention the Kometan Formation and recorded the presence of erosional unconformity (missing sediment of Santonian-Middle Campanian) under Shiranish Formation. The location of the type section is not clear and it is combination of the three different sections in three different areas which are located in the imbricated Zone. Topographically and structurally, the section is so complex that a nowadays geologists will never think to select it as a type section for definition a stratigraphical units.
Keywords: Balambo Formation,Kometan Formation,Sirwan valley,unconformity,Gulneri Formation